2020
DOI: 10.1080/17477891.2020.1772188
|View full text |Cite
|
Sign up to set email alerts
|

Gulf Coast parents speak: children’s health in the aftermath of the Deepwater Horizon oil spill

Abstract: This paper examines the physical and mental health of children following the Deepwater Horizon oil spill (DHOS). A multi-stage sampling design was used to select households for inclusion in the study. Data were obtained from parental interviews (n = 720) in the harder-hit areas of Louisiana in the US Gulf Coast. Three out of five parents reported that their child had experienced physical health symptoms and nearly one third reported that their child had mental health issues since the oil spill. Both direct phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Beedasy et al's cross-sectional study in areas of Louisiana impacted by DHOS, predicated on the sampling frame of the four-state Gulf Coast Population Impact (GCPI) study, found that three out of five and nearly one-third of children experienced physical and mental health issues, respectively, and that these were significantly predicted by physical and household economic DHOS exposure. 16 A longitudinal extension of this study in southern Louisiana by Slack, et al found that familial physical and economic oil spill exposure negatively influenced initial child health, and the effects of job or income loss persisted. 17 Studies of Louisiana and Mississippi adolescents found significant associations between oil spill-related stress and post-traumatic stress disorder and poor self-reported competence and well-being.…”
Section: Introductionmentioning
confidence: 60%
“…Beedasy et al's cross-sectional study in areas of Louisiana impacted by DHOS, predicated on the sampling frame of the four-state Gulf Coast Population Impact (GCPI) study, found that three out of five and nearly one-third of children experienced physical and mental health issues, respectively, and that these were significantly predicted by physical and household economic DHOS exposure. 16 A longitudinal extension of this study in southern Louisiana by Slack, et al found that familial physical and economic oil spill exposure negatively influenced initial child health, and the effects of job or income loss persisted. 17 Studies of Louisiana and Mississippi adolescents found significant associations between oil spill-related stress and post-traumatic stress disorder and poor self-reported competence and well-being.…”
Section: Introductionmentioning
confidence: 60%
“…An established and growing body of research has demonstrated the negative impacts of oil spills in terms of psychosocial stress among affected populations (Gill et al, 2016; Palinkas et al, 1993). In the context of the DHOS, spill exposure has been variously associated with psychological outcomes such as depression, anxiety, and worry (Ayer et al, 2019; Beedasy et al, 2021; Cope et al, 2013, 2016; Gill et al, 2014; Lee & Blanchard, 2012; Osofsky et al, 2011; Parker et al, 2020; Ramchand et al, 2019; Rung et al, 2016). The findings reported here dovetail most specifically with previous research elucidating linkages between economic DHOS exposure and negative impacts on health variously defined (Parks et al, 2020; Peres et al, 2016; Slack et al, 2021; Stroope et al, 2021) and speak directly to the limited research focused on psychological resilience as an outcome specifically (Lightfoot et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such stress can stem from direct contact with toxic substances as well as the broader disruption of people’s socioeconomic circumstances and way of life, including job loss and involvement in protracted litigation (Keating et al, 2020; Ritchie et al, 2018). Accordingly, DHOS exposure—physical and socioeconomic—has been variously associated with outcomes such as depression, anxiety, worry, and substance abuse (Ayer et al, 2019; Beedasy et al, 2021; Cope et al, 2013, 2016; Drakeford et al, 2020; Gill et al, 2014; Lee & Blanchard, 2012; Osofsky et al, 2011; Parker et al, 2020; Parks et al, 2018; Ramchand et al, 2019; Rung et al, 2016). Economic DHOS exposure (e.g., job and income loss, occupational threat) has also been shown to have particularly pernicious effects on well-being (Parks et al, 2020; Slack et al, 2021; Stroope et al, 2021).…”
mentioning
confidence: 99%
“…Six focus groups were conducted in the following Louisiana parishes: Vermilion, Terrebonne, Lafourche, Plaquemines, Orleans, and St. Tammany. Portions of these parishes were identified as heavily impacted by the DHOS, and a probability sample of households with children was developed for a multiwave survey (for more details on the sampling design, see Abramson et al, 2013; Beedasy et al, 2020). In November 2017, focus group participants were drawn from a larger sample of 484 survey participants.…”
Section: Methodsmentioning
confidence: 99%
“…Work disruption for individuals and family members following a technological disaster can be exacerbated by stressful litigation and compensation claims, lack of institutional trust, increased perception of risk, and perceptions of chronic community damage (Picou et al, 2004; Ritchie et al, 2013). Following the DHOS, research has connected exposure to spill‐related economic loss with negative health outcomes for children in both the medium term (Beedasy et al, 2020) and long term (Slack et al, 2020).…”
Section: Introductionmentioning
confidence: 99%